Normative distinction between illegal trafficking of persons across the Ukrainian state border from related criminal offenses - Shekhter, Serhii (Migration & Law, 2025)
The article is devoted to analysis of the features of the normative differentiation of the corpus delicti of criminal offense provided for in Article 332 of the Criminal Code of Ukraine from related criminal offenses. The relevance of the study is determined by the presence of problems in law enforcement practice regarding the qualification of acts related to the organization of illegal trafficking of persons across the state border of Ukraine, which is caused by the similarity of the objective and subjective elements of related offenses, as well as the ambiguity of their normative regulation. The study conducts a systematic examination of the elements of the corpus delicti of the criminal offense under Article 332 of the Criminal Code of Ukraine, focusing on the object, the objective side, the subject, and the subjective side, and identifies key criteria for distinguishing it from related criminal offenses, in particular those provided for in Articles 149, 332-1, 332-2, 358, and other provisions of the Criminal Code of Ukraine. Special attention is paid to clarifying the content of features such as the method of committing the act, the purpose and motive of criminal behavior, the form of guilt, and the nature of socially dangerous consequences. It is emphasized that the illegal trafficking of persons across the state border has an independent direct object and does not cover cases of illegal border crossing without a specific intent to harm the interests of the state, which entails administrative liability. The study separately considers issues of qualification in cases where trafficking is combined with the exploitation of persons, document forgery, or corruption-related acts, which requires the application of the rules of cumulative criminal offenses. The conclusion is drawn that effective law enforcement of Article 332 of the Criminal Code of Ukraine is possible only under the condition of a comprehensive consideration of the objective and subjective elements of the offense and strict adherence to the criteria for its differentiation from related offenses, which is of fundamental importance for ensuring the consistency of judicial practice and the rule of law in criminal law.